2012
DOI: 10.1097/yic.0b013e3283589a3f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of duloxetine treatment on functioning as measured by the Sheehan disability scale

Abstract: The purpose of this work is to describe the effect of duloxetine on functioning as measured by the Sheehan disability scale (SDS) compared with placebo in patients with major depressive disorder (MDD). Pooled data from six randomized, parallel, double-blind, placebo-controlled duloxetine studies in adult MDD patients were analyzed at the short-term (7-13 weeks) and the long-term (>24 weeks) endpoint. The primary variable was the SDS total score. Secondary variables included functional remission (SDS total ≤ 6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…The SDS is a validated measure of functional impairment that has demonstrated sensitivity to impairment and the effects of treatment across a wide range of disorders, including MDD (Sheehan & Sheehan, 2008). The SDS has been used to assess functional improvement in association with improvements in depressive symptoms for duloxetine (Mancini et al., 2012; Oakes et al., 2012; Sheehan et al., 2011; Wise et al., 2008), desvenlafaxine (Dunlop et al., 2011; Guico‐Pabia et al., 2012; Soares et al., 2009), paroxetine (Wise et al., 2008), bupropion (Hewett et al., 2010; Soczynska et al., 2014), escitalopram (Romera et al., 2012; Soczynska et al., 2014), venlafaxine (Fann et al., 2015; Hewett et al., 2010), levomilnacipran (Asnis et al., 2013; Sambunaris, Bose, et al., 2014), and agomelatine (Montgomery, Nielsen, et al., 2014; Zajecka et al., 2010) with results that have been variable with respect to clinical significance; however, many of these antidepressants showed significant differences versus placebo in the change from baseline versus placebo in the SDS total score when patients were stratified by baseline depressive symptom severity. A recent pooled analysis showed that treatment with duloxetine ( n  = 1,029) and SSRIs ( n  = 835) resulted in significantly greater improvements in the SDS total score (∆ −1.9, p  <   .001; ∆ −1.7, p  <   .01, respectively) compared to placebo ( n  = 329).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDS is a validated measure of functional impairment that has demonstrated sensitivity to impairment and the effects of treatment across a wide range of disorders, including MDD (Sheehan & Sheehan, 2008). The SDS has been used to assess functional improvement in association with improvements in depressive symptoms for duloxetine (Mancini et al., 2012; Oakes et al., 2012; Sheehan et al., 2011; Wise et al., 2008), desvenlafaxine (Dunlop et al., 2011; Guico‐Pabia et al., 2012; Soares et al., 2009), paroxetine (Wise et al., 2008), bupropion (Hewett et al., 2010; Soczynska et al., 2014), escitalopram (Romera et al., 2012; Soczynska et al., 2014), venlafaxine (Fann et al., 2015; Hewett et al., 2010), levomilnacipran (Asnis et al., 2013; Sambunaris, Bose, et al., 2014), and agomelatine (Montgomery, Nielsen, et al., 2014; Zajecka et al., 2010) with results that have been variable with respect to clinical significance; however, many of these antidepressants showed significant differences versus placebo in the change from baseline versus placebo in the SDS total score when patients were stratified by baseline depressive symptom severity. A recent pooled analysis showed that treatment with duloxetine ( n  = 1,029) and SSRIs ( n  = 835) resulted in significantly greater improvements in the SDS total score (∆ −1.9, p  <   .001; ∆ −1.7, p  <   .01, respectively) compared to placebo ( n  = 329).…”
Section: Discussionmentioning
confidence: 99%
“…(2008) and Sheehan et al. (2011) and which has been used in other studies of MDD to define functional remission (Mancini et al., 2012; Montgomery, Mansuy, et al., 2014; Sambunaris, Bose, et al., 2014; Sambunaris, Gommoll, et al., 2014; Soares et al., 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Despite recent focus on assessing functional impairment as an important ‘real-world’ outcome of antidepressant treatment (Zimmerman et al , 2006; Sheehan and Sheehan, 2008; Soares et al , 2009; Langlieb and Guico-Pabia, 2010; Sheehan et al , 2011; Mancini et al , 2012), there have been relatively few studies examining whether there are baseline characteristics that predict the likelihood of improved functional impairment during treatment. One recent post-hoc analysis of a large pool of data from studies on the SNRI duloxetine versus placebo reported that female sex, a shorter time since the first depressive episode, absence of previous antidepressant use, and mild versus more severe pain were all prognostic factors for improved functioning following antidepressant treatment (Mancini et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One recent post-hoc analysis of a large pool of data from studies on the SNRI duloxetine versus placebo reported that female sex, a shorter time since the first depressive episode, absence of previous antidepressant use, and mild versus more severe pain were all prognostic factors for improved functioning following antidepressant treatment (Mancini et al , 2012). Guico-Pabia et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation